PENGARUH MULTIMEDIA INTERAKTIF BERBASIS CANVA TERHADAP KEMAMPUAN BERPIKIR KRTISIS MATEMATIS PADA MATERI ANALISIS DATA - Sani Syailawati Hanifah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
At this time, the independent curriculum emphasizes that there needs to be the best service that can facilitate all the needs of students. This prompted SDN 195 Isola to agree to group students based on their needs in one class. This drives class I C at SDN 195 Isola to have a higher grade of need at their level. Teachers need to provide a higher level of challenge, so students feel challenged in each lesson. This study aims to investigate the effect of Canva-based interactive multimedia on students' ability to think critically mathematically in the subject of mathematics elements of data analysis. Researchers used the Classroom Action Research method with the Kemmis and McTaggart designs. The students involved in the current research were first graders at SDN 195 Isola, with 29 students. The material used is data material using pictograms and scales. The results of the study show that the use of Canva-based interactive multimedia has a significant effect on improving mathematical critical thinking skills. According to John Butterworth, the increase in student learning outcomes can be seen from the results measured by using an instrument test to test students' mathematical critical thinking skills using critical thinking indicators, namely analysis, evaluation, and further arguments. The instrument is given before the action, which results in the average value of this cycle getting a value of 41. Then the same test instrument is given after implementing the students' actions from this posttest, getting an average value of 78.70.